"Education First" or "Tourism First" - What Influences the Choice of Location for International Exchange Students: Evidence from Poland - Kosmaczewska, Joanna; Jameson, Stephanie (Journal of hospitality & tourism education, 2023)
Although the main purpose of international student mobility is to study, it can also be considered a type of tourist activity. The purpose of this study is to identify and profile international exchange students by their attitudes toward education and traveling during their exchange programmes. This study adds to the literature in the field of "study abroad programmes" in three important ways. First, this study focuses on incoming students, whereas the vast majority of studies on study abroad/exchange students focus solely on the outgoing community. Second, this study describes two types of international exchange students, identified based on their attitudes toward "education first" and "tourism first." Finally, it identifies the predictor variables that significantly distinguish between international exchange students' preferences for "education first" or "tourism first." Finally, the combination of these three factors offers a unique perspective on a student population and on constructs that have received very little focus in research published to date. The study found that these students were motivated by "tourism first" rather than pursuing study goals in foreign countries and this decision was based on factors such as personal savings, anticipated duration of study in Poland and the student's home country.